Long-Term Trends in Public Finances in the G-7 Economies - Schaechter, Andrea; Cottarelli, Carlo (Washington, D.C. : International Monetary Fund, 2010)
Today's record public debt levels in most advanced economies are not only a direct fall-out from the global crisis. Public debt had ratcheted up over many decades before, when it had been used, in most of the G-7 countries, as the ultimate shock absorber-rising in bad times but not declining much in good times. Alongside, primary spending increased, particularly during 1965-85, reflecting predominantly a surge in health care and pension spending. Looking ahead, advanced economies will face the formidable challenge of reducing debt ratios at a time when ageing-related spending, in particular often underestimated pressures from health care systems, will put additional pressure on public finances. Addressing these fiscal challenges will require growth-friendly structural reforms, a fiscal strategy involving gradual but steady fiscal adjustment, stronger fiscal institutions, expenditure and revenue reforms, and an appropriate degree of burden sharing across all stakeholders.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet